Serum IL-33, a new marker predicting response to rituximab in rheumatoid arthritis. Issue 1 (December 2016) - Sellam, Jérémie; Rivière, Elodie; Courties, Alice; Rouzaire, Paul-Olivier; Tolusso, Barbara; Vital, Edward; Emery, Paul; Ferracioli, Gianfranco; Soubrier, Martin; Ly, Bineta; Hendel Chavez, Houria; Taoufik, Yassine; et al.
Abstract Background Recent works have suggested a possible link between interleukin (IL)-33 and B-cell biology. We aimed to study the possible association between serum IL-33 detection and response to rituximab (RTX) in rheumatoid arthritis (RA) patients in different cohorts with an accurate enzyme-linked immunosorbent assay (ELISA). Methods Serum IL-33, rheumatoid factor (RF), anti-cyclic citrullinated peptide (anti-CCP), and high serum immunoglobulin (Ig)G levels were assessed in 111 RA patients receiving a first course of 2 g RTX (cohort 1) in an observational study and in 74 RA patients treated with the same schedule in routine care (cohort 2). Univariate and multivariate analyses identified factors associated with a European League Against Rheumatism (EULAR) response at 24 weeks. Results At week 24, 84/111 (76%) and 54/74 (73%) patients reached EULAR response in cohorts 1 and 2, respectively. Serum IL-33 was detectable in only 33.5% of the patients. In the combined cohorts, the presence of RF or anti-CCP (odds ratio (OR) 3.27, 95% confidence interval (CI) 1.13–9.46;p = 0.03), high serum IgG (OR 2.32, 95% CI 1.01–5.33;p = 0.048), and detectable serum IL-33 (OR 2.40, 95% CI 1.01–5.72;p = 0.047) were all associated with RTX response in multivariate analysis. The combination of these three factors increased the likelihood of response to RTX. When serum IL-33 detection was added to seropositivity and serum IgG level, 100% of the patients with the three risk factors (corresponding to 9% of the population) responded to RTX (OR versus patients with none of the three risk factors 29.61, 95% CI 1.30–674.79;p = 0.034). Conclusion Detectable serum IL-33 may predict clinical response to RTX independently of, and synergistically with, auto-antibodies and serum IgG level. Trial registration NCT01126541 ; 18 May 2010.